2018
DOI: 10.1158/1535-7163.mct-17-1299
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Systemic Therapies in Clear Cell Renal Cell Carcinoma: Mechanisms and Management Strategies

Abstract: Renal cell carcinoma (RCC) is the most common form of kidney cancer. It is categorized into various subtypes, with clear cell RCC (ccRCC) representing about 85% of all RCC tumors. The lack of sensitivity to chemotherapy and radiation therapy prompted research efforts into novel treatment options. The development of targeted therapeutics, including multi-targeted tyrosine kinase inhibitors (TKI) and mTOR inhibitors, has been a major breakthrough in ccRCC therapy. More recently, other therapeutic strategies, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
311
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(316 citation statements)
references
References 117 publications
(144 reference statements)
3
311
0
2
Order By: Relevance
“…N‐linked glycosylation is only one component of the complex glycan functions in normal and diseased kidneys that include many roles for O‐linked glycans, glycosaminoglycans, and glycolipids . Because of the critical need to improve outcomes for promising immunotherapy and angiogenesis targeted treatments for ccRCC that work in subsets of patients, continued evaluation of N‐linked glycosylation and other glycan classes in this context could provide new therapeutic and diagnostic assay leads.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…N‐linked glycosylation is only one component of the complex glycan functions in normal and diseased kidneys that include many roles for O‐linked glycans, glycosaminoglycans, and glycolipids . Because of the critical need to improve outcomes for promising immunotherapy and angiogenesis targeted treatments for ccRCC that work in subsets of patients, continued evaluation of N‐linked glycosylation and other glycan classes in this context could provide new therapeutic and diagnostic assay leads.…”
Section: Resultsmentioning
confidence: 99%
“…Renal cell carcinoma derived from epithelial tubular cells represents 90% of kidney cancers, and clear‐cell renal cell carcinoma (ccRCC) is the most prevalent subtype comprising 70% to 80% of cases . Typically, ccRCC is detected at advanced stages and, in general, is highly resistant to standard chemotherapy and radiotherapy treatments leading to high rates of recurrence and mortality . The histopathological hallmark of ccRCC is a clear cytoplasm appearance, because of accumulation of multiple lipids and glycogen, associated with Warburg effect metabolism .…”
Section: Introductionmentioning
confidence: 99%
“…Unpredictable response to treatment represents one of the most controversial issues in cc RCC. Resistance to therapy is based on an incomplete mechanism of action (21), and there is no effective definitive therapeutic tool available (22). Lichner et al recently reported that Sunitinib therapy for advanced RCC induces selection of a tumor cells subpopulation able to survive and to grow as spheroids in tumor models xenografts (23).…”
mentioning
confidence: 99%
“…This observation may be due to the special pathological type of PCCCL. Similarly, traditional chemo-and radio-therapy are largely ineffective in treating any renal cell carcinoma subtype, and the underlying mechanistic reasons need to be further explored [42].…”
Section: Discussionmentioning
confidence: 99%